Status gizi, kadar hemoglobin, ureum, dan kreatinin pasien konseling gizi hemodialisa - Kristiawan P. A. Nugroho; Sarlina Palimbong; Fransiska M. Santoso Putri; Puji Astuti; Ike Listiyowati (Jurnal Gizi dan Dietetik Indonesia (Indonesian Journal of Nutrition and Dietetics), 2017)
ABSTRACTBackground : Patients who are undergoing hemodialysis therapy must know which foods that may be consumed including foods containing animal protein, low potassium, and low salt. The role of nutritionists is needed to provide nutritional counseling related to dietary adjustment. Studies that have been conducted by previous researchers are about diet from hemodialysis patients and the various factors that affect dietary compliance of patients, but no one has been studying the relation related to nutritional status, hemoglobin, ureum, and creatinine levels before and after doing a counseling that also has a relationship with diet and dietary compliance for hemodialysis patients.Objectives : To analyze the relationship of nutritional status, hemoglobin, ureum, and creatinine levels of hemodialysis patients before and after doing nutritional counseling in RSUD Ungaran. Methods : The study used a descriptive quantitaive method with one group pretest posttest design with cross sectional approach. The research was conducted in Hemodialysis Unit of RSUD Ungaran with a total sampling of 30 hemodialysis patient. Primary data were obtained from respondent’s data entry and FFQ, observation, and interviews. Secondary data were obtained from respondent’s medical records include the level of hemoglobin, urea, and cretinine. Data were analyzed using SPSS programme with Paired t Test. Results : The results of SPSS analysis showed that probability value from urea men 0,016 < 0,05 and urea women – hemoglobin men and women – creatinin men and women overall 0,000 < 0,05, which means that the average levels of those components before and after doing a nutritional counseling is different.Conclusions : A nutritional counseling indicate any change in the nutritional status of the entire hemodialysis patients, based on hemoglobin levels increased, while urea and creatinine levels decreased; but all those components are not in the normal category. Levels of hemoglobin, urea, and creatinine is changed within a period of one month after the implementation of individual nutritional counseling. It indicates that nutritional counseling efforts were given has a positive benefit for the patients to gain knowledge about dietary adjustments and implement the recommended diet in order to optimize the work of renal function excessively.KEYWORDS : nutritional status, hemodialysis, eating behavior, nutritional counseling